Violence Hyperreality Message in Dating Relationship in Digital Text on Joylada Application - Suprihatin - -; Riesta Ayu Oktarina (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2022)
AbstractJoylada is a fiction reading application which is based on the technology can be downloaded via Android, iPhone or personal computer. The scientists observed, some fiction in Joylada application that has romantic genre and sexuality theme are considered attractive by the readers. The one that attracts the observer is the efforts to convey the messages that violence towards female when they engage in a dating relationship is a common thing. This is portrayed in an interview that is constructed by writers through their novels. Two novels are chosen in this research entitled Aku Bukan Budak Seksmu and My Sweet Psikopat. The objects are studied using Critical Discourse Analysis method by Teun A. Van Dijk to see how violence in dating relationship is constructed as a hyperreality to naturalize the message behind the discourse. From the research result, data are obtained that violence in dating relationship is brought as the main topics by the text producers in both novels. This is supported by relevant subtopics. In social cognition level, violence discourse in both novels is the perspective of the writer about violence. Meanwhile, in social analysis level, discourse about violence and sexual violence in both novels cannot be accepted by the readers. Yet, it is a different story if the character who did it is portrayed as a man with ideal physical image, settled and psychopath-masked. Abstrak Joylada adalah aplikasi bacaan fiksi berbasis teknologi yang dapat diunduh melalui Android, iPhone, atau komputer pribadi. Para ilmuwan mengamati, beberapa fiksi dalam aplikasi Joylada yang bergenre romantis dan bertema seksualitas dinilai menarik oleh pembaca. Salah satu yang menarik perhatian peneliti adalah upaya menyampaikan pesan bahwa kekerasan terhadap perempuan ketika mereka menjalin hubungan pacaran adalah hal yang lumrah. Hal ini tergambar dalam sebuah wawancara yang dikonstruksi oleh para penulis melalui novel-novel mereka. Dua novel yang dipilih dalam penelitian ini berjudul Aku Bukan Budak Seksmu dan My Sweet Psikopat. Objek-objek tersebut dikaji dengan menggunakan metode Analisis Wacana Kritis oleh Teun A. Van Dijk untuk melihat bagaimana kekerasan dalam hubungan pacaran, dikonstruksi sebagai sebuah hiperrealitas untuk menaturalisasi pesan di balik wacana tersebut. Dari hasil penelitian diperoleh data bahwa kekerasan dalam hubungan pacaran diangkat sebagai topik utama oleh produser teks dalam kedua novel tersebut. Ini didukung oleh subtopik yang relevan. Dalam tataran kognisi sosial, wacana kekerasan dalam kedua novel tersebut merupakan perspektif penulis tentang kekerasan. Sedangkan pada tataran analisis sosial, wacana tentang kekerasan dan kekerasan seksual dalam kedua novel tersebut tidak dapat diterima oleh pembaca. Namun lain cerita jika tokoh yang melakukannya digambarkan sebagai pria dengan citra fisik ideal, mapan, dan bertopeng psikopat.